English Grammar in use Supplenentary Exercises with Answers - Hashemi, Louise (Cambridge University, 1995)
To the students: The book has 158 excercises. Each excercises relates to a prarticular part of English Grammar in use. You can find the English grammar in use in the top right - hand corner of each page. You can use this book if you don't have English grammar in use because all the answers, with lost of alternatives, are given in the Key. But if you want an explanation of the grammar points, you will need to check in English grammar in use. The grammar points covered in the book are not in order of difficulty, so you can go straight to the parts where you need most practice. Where there are serveral excercises on one grammar points, however, you will find that the easier ones come first. It is a good idear to try one excercises, check your answer and then go on the next one. To the teacher: English grammar in use supplemetary excercises offers extra practice of most of the grammar covered in English grammar in use. Much of the language is contextualised within dialogues, letters, articles, ...encouraging students to consider meaning as well as form. The book can be used as self-study material or as a basic for further practice in class or as homework....